Richard C. Blum, Dianne Feinstein and Milton Marks - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows Richard C. Blum walking to the right of Dianne Feinstein, (in light striped shirt), and State Senator Milton Marks on her left during a candlelight march in remembrance of Harvey Milk and George Moscone who had been assasinated by Dan White. A banner in the background reads, "[illegible] Gay power, Harvey Milk lives".